New genetic loci implicated in fasting glucose homeostasis and their impact on type 2 diabetes risk - Jackson, Anne U; Wheeler, Eleanor; Bouatia-Naji, Nabila; Morris, Andrew P; Rybin, Denis; Thorleifsson, Gudmar; Steinthorsdottir, Valgerdur; Grallert, Harald; Dehghan, Abbas; Franklin, Christopher S; Song, Kijoung; Egan, Josephine M; et al. (Nature genetics, 2010)
The MAGIC investigators report results of a large genome-wide association study meta-analysis to identify common variants influencing fasting glucose homeostasis. They further show that several of the newly discovered loci influencing glycemic traits are also associated with risk of type 2 diabetes. Levels of circulating glucose are tightly regulated. To identify new loci influencing glycemic traits, we performed meta-analyses of 21 genome-wide association studies informative for fasting glucose, fasting insulin and indices of beta-cell function (HOMA-B) and insulin resistance (HOMA-IR) in up to 46,186 nondiabetic participants. Follow-up of 25 loci in up to 76,558 additional subjects identified 16 loci associated with fasting glucose and HOMA-B and two loci associated with fasting insulin and HOMA-IR. These include nine loci newly associated with fasting glucose (in or near ADCY5 , MADD , ADRA2A , CRY2 , FADS1 , GLIS3 , SLC2A2 , PROX1 and C2CD4B ) and one influencing fasting insulin and HOMA-IR (near IGF1 ). We also demonstrated association of ADCY5 , PROX1 , GCK , GCKR and DGKB-TMEM195 with type 2 diabetes. Within these loci, likely biological candidate genes influence signal transduction, cell proliferation, development, glucose-sensing and circadian regulation. Our results demonstrate that genetic studies of glycemic traits can identify type 2 diabetes risk loci, as well as loci containing gene variants that are associated with a modest elevation in glucose levels but are not associated with overt diabetes.